Where We Have Been and Where We Can Go From Here: Looking to the Future in Research on Media, Race, and Ethnicity. (March 2015) - Tukachinsky, Riva; Mastro, Dana; Tukachinsky, Riva
<x xml:space="preserve">Abstract</x> This special issue illuminates the ways in which media portrayals and practices, together, create barriers to inclusion for diverse groups and normalize existing patterns of relegation on and off the screen. Media representations of race and ethnicity have critical consequences for intergroup relationships and for marginalized group members' self‐concept. A synthesis of the research included in this volume demonstrates the significance of these questions across media outlets, their relevancy despite the rise of new technologies, and their application to social contexts outside the United States. Finally, this concluding article suggests directions for future research and offers implications for policies that can foster prosocial outcomes.